# Showing that the cardinal $\mu=\min\{\lambda: \kappa^{\lambda} > \kappa\}$ is regular

How to show that for $\kappa\geq\aleph_0,$ $\mu=\min\{\lambda: \kappa^{\lambda} > \kappa\}$ is regular?

If I wanted a contradiction, it would suffice to prove $\kappa^{cf(\mu)}>\kappa$, but I don't see how this could be true.

• $k^{cf(k)}>k$ for every infinite cardinal $k$. This is Konig's Theorem, sometimes called Konig's Lemma. But $cf(k)$ is not necessarily the least $l$ such that $k^l>k$. Apr 24, 2016 at 5:47

Let $\kappa$ be infinite and $\mu=\min\{\lambda\mid \kappa^\lambda>\kappa\}$ (this cardinal exists, since already $\kappa^\kappa>\kappa$). If $\mu$ is singular, write $\mu=\sum_{\alpha<\theta}\mu_\alpha$ where $\theta={\rm cf}(\mu)<\mu$ and the $\mu_\alpha$ form a strictly increasing sequence of regular cardinals. We have $$\kappa^\mu=\kappa^{\sum_\alpha \mu_\alpha}=\prod_\alpha \kappa^{\mu_\alpha}.$$ Now, by definition of $\mu$, $\kappa^{\mu_\alpha}=\kappa$ for all $\alpha$, and therefore the product above reduces to $\prod_\alpha\kappa=\kappa^\theta$. Again, since $\theta<\mu$, then $\kappa^\theta=\kappa$, and we are done.
The key equality is of course $\kappa^{\sum_\alpha \mu_\alpha}=\prod_\alpha \kappa^{\mu_\alpha}$, which is proved directly: The sum $\sum_\alpha\mu_\alpha$ is the cardinality of the disjoint union $\bigcup_\alpha \mu_\alpha\times\{\alpha\}$, and we can identify any function $\phi$ from this union to $\kappa$ with the sequence of functions $(\phi_\alpha\mid \alpha<\theta)$ given by $\phi_\alpha=\phi\upharpoonright \mu_\alpha\times\{\alpha\}$. This is actually a bijection between ${}^{\bigcup_\alpha \mu_\alpha\times\{\alpha\}}\kappa$ and the Cartesian product $\prod_\alpha {}^{\mu_\alpha\times\{\alpha\}}\kappa$.
• Note that the "key equality" follows from abstract nonsense in any cartesian closed category : $Hom(-,\kappa^{\displaystyle\sum_\alpha \mu_\alpha}) \cong Hom(- \times \displaystyle\sum_\alpha \mu_\alpha, \kappa ) \cong \displaystyle\prod_\alpha Hom(-\times \mu_\alpha, \kappa) \cong \displaystyle\prod_\alpha Hom(-, \kappa^{\mu_\alpha}) \cong Hom(-, \displaystyle\prod_\alpha \kappa^{\mu_\alpha})$, and we can conclude by the Yoneda Lemma (the fact that the product commutes with the direct sum comes from a classical application of Yoneda). These hold whenever the product and coproduct exist. Dec 20, 2017 at 19:00